2020
DOI: 10.1111/dme.14241
|View full text |Cite
|
Sign up to set email alerts
|

Non‐attendance at diabetes outpatient appointments: a systematic review

Abstract: Background Non-attendance at diabetes outpatient appointments is a sizeable problem worldwide and has been associated with suboptimal health outcomes. We aimed to describe the characteristics, health outcomes and reasons given for non-attendance at doctor-or nurse-led diabetes appointments, and interventions to improve attendance. Methods PubMed, EMBASE, CINAHL and PsychInfo were searched from database inception to February 2019. Included articles were peer-reviewed, published in English, related to adults or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 46 publications
4
88
0
Order By: Relevance
“…Patient navigators are a resource-intensive approach to increase attendance rates but have been successful at some clinics [8,11,19], with navigators being able to both identify reasons for non-attendance and improving patients' understanding of their need for appointments through personalized education. A major challenge to implementing this approach is the financial cost of a navigator to the clinic because they must be well educated on the services available at the clinic and in the community, as well as having a considerable time to work with patients to access these services.…”
Section: Discussionmentioning
confidence: 99%
“…Patient navigators are a resource-intensive approach to increase attendance rates but have been successful at some clinics [8,11,19], with navigators being able to both identify reasons for non-attendance and improving patients' understanding of their need for appointments through personalized education. A major challenge to implementing this approach is the financial cost of a navigator to the clinic because they must be well educated on the services available at the clinic and in the community, as well as having a considerable time to work with patients to access these services.…”
Section: Discussionmentioning
confidence: 99%
“…A healthcare appointment may not coincide with when an individual most needs help or support, and there are several reasons why an individual with diabetes may become ‘hardly reached’. It has been well described that ‘hardly reached’ individuals are at increased risk of diabetes-related complications 23…”
Section: Opportunities For Community Pharmacists In Diabetes Carementioning
confidence: 99%
“…Recent systematic reviews found that non-participation in outpatient settings were related to appointment logistical issues, such as lack of exibility in the outpatient clinic and communication failures as well as socioeconomic and psychological factors (5,6). Additionally, Lee et al found that non-participation was associated with younger age, smoking and higher HbA 1c (6).…”
Section: Introductionmentioning
confidence: 99%
“…From an individual's perspective, a systematic review found reasons for non-participation in diabetes outpatient clinics could be categorised into I) poor relationship with the healthcare professionals (HPs), II) low perceived bene ts of participating and balancing the costs, and III) coping strategies like handing over management of diabetes to family members in particular (5). By contrast, people with T2D who previously participated in diabetes clinical trials expressed both altruism and self-interest as motives for participating (8).…”
Section: Introductionmentioning
confidence: 99%